Factors affecting location decisions of the economic headliners - exporters and foreign-owned firms - in China - Natalia Trofimenko (Kiel Institute for the World Economy (IfW), 2010)
Foreign-owned firms are frequently viewed as an important source of new capital, access to world markets and employment generation and there exist numerous studies on the determinants of FDI flows and the role of incentives designed to attract FDI. Similarly important for economic growth are exporters, yet the factors that play a role in their location decisions have not been identified. Using a data set of 1,409 firms in China who report, among other things, why they have chosen a particular location, we find that the perceived importance of various site attributes differs considerably for those two types of firms: foreign-owned firms are attracted by the local market size, supply of skilled workers, and the quality of (telecommunications!) infrastructure; future exporters are driven by low rents, and fewer regulatory requirements and taxes; both types of firms care about the availability of government services.
Keywords: R3; R11; F21; L10; 330; Foreign direct investment; exporters; determinants of location; Chinese cities; Direktinvestition; Multinationales Unternehmen; Exportindustrie; Standortwahl; Standortfaktor; China